PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 003 BANTAYAN BARU - Susilawati B '; Eddy Noviana; Zufriady ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Intent of observational it is subject to be increase IPS studying result by applying kooperatif learning model type Make A Match on student Class V in SDN 003 Bantayan Baru. On this research mengunakan methodics Action Research braze (PTK) with subjek research is student brazes v SDN 003 Bantayan New that total 22 student. menunjukan's observational result increases it activity learns on meet i. cycle first which is 58,30% by enough categories, then increasing on appointment second becomes 66,70 % get categories well. On cycle II. appointment first increases 79,20% by good categories, then on appointment second increases again 95,80% by good categories. Student activity result on meet i. cycle percentage first 58,30% get enough categories, then on second appointment 66,70% also get categories well, on cycle II. first appointment 75% get categories well, on second Cycle appointment II. also experience step-up 87,50 % by ketegori well. Students learned thoroughness on base score, complete student just 9 students whereas that don't complete 13 students, with klasikal's thoroughness 40,91 % (are not complete). On cycles daily dry run i. student which complete 14 students whereas that don't complete 8 students, with klasikal's thoroughness 63,63 % (are not complete). Meanwhile on cycles daily dry run II. experience thoroughness step-up, complete student 21 person, meanwhile that don't complete 1, with klasikal's thoroughness 95,45%.Key word : Model Kooperatif is Type Make A Match, IPS Learned result